2015
DOI: 10.1002/ajh.24025
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the diagnosis of heparin‐Induced thrombocytopenia: A 6‐year experience from a reference laboratory

Abstract: Heparin-induced thrombocytopenia (HIT) is caused by platelet-activating antibodies against complexes of platelet factor 4 (PF4) and heparin. The diagnosis of HIT is contingent on accurate and timely laboratory testing. Recently, alternative anticoagulants for the treatment of HIT have been introduced along with algorithms for better HIT diagnosis. However, the increased reliance on immunoassays for the diagnosis of HIT may have harmful consequences due to the high rate of false positive results. To compare tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…The disparities between anti‐PF4/heparin antibodies that activate platelets (pathogenic HIT antibodies) and those that do not (non‐pathogenic anti‐PF4/heparin antibodies) present a significant challenge in diagnosing HIT patients . This is because of the absence of a rapid and widely available laboratory diagnostic test with high specificity that can distinguish pathogenic from non‐pathogenic antibodies .…”
Section: Introductionmentioning
confidence: 99%
“…The disparities between anti‐PF4/heparin antibodies that activate platelets (pathogenic HIT antibodies) and those that do not (non‐pathogenic anti‐PF4/heparin antibodies) present a significant challenge in diagnosing HIT patients . This is because of the absence of a rapid and widely available laboratory diagnostic test with high specificity that can distinguish pathogenic from non‐pathogenic antibodies .…”
Section: Introductionmentioning
confidence: 99%
“…The 14 samples that were positive in the PF4‐SRA had a significantly higher OD value in the EIA compared with the 25 samples that remained negative in the PF4‐SRA. In addition, we recently reported that although high OD values in the EIA can predict SRA reactivity (93% of samples with OD 405 >2.0 are SRA‐positive), there remains a subset of samples (7%) that will have a negative SRA result even in the presence of high OD 405 values . Similarly, in this study, three of the EIA‐positive/SRA‐negative samples that were negative in the PF4‐SRA actually had the highest OD 405 values in the EIA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence to support the need for a critical titer of HIT antibodies are that (i) high titers of anti‐PF4/heparin antibodies strongly correlate with positive results in HIT functional assays ; (ii) high titers of anti‐PF4/heparin antibodies precede the onset of thrombocytopenia and thrombosis in patients with HIT by a median of 2 and 5.5 days, respectively ; and (iii) ~88% of patients who are positive in the SRA have sufficient levels of platelet‐activating antibodies to cause > 50% release in the SRA . Therefore, a threshold level of platelet‐activating anti‐PF4/heparin antibodies might be required to initiate in vivo platelet activation and subsequently trigger HIT.…”
Section: Introductionmentioning
confidence: 99%
“…For moderate or high scores, further testing is recommended, and the patient started on alternative anticoagulation until the diagnosis can be conclusively excluded. The absence of PF4 IgG antibodies has a high negative predictive value and rules out HIT; specificity is poor so positive tests require additional analysis [142][143][144][145]. Serotonin release assay has high specificity (95-100 %) and positive predictive value for HIT; however, the availability is limited.…”
Section: Drug-induced Thrombocytopeniamentioning
confidence: 99%